Online verbal aggression on interpersonal trust among college students: the chain-mediating effect of core self-evaluation and emotional intelligence - Yao, Yao; Fan, Xuejun; Chen, Gang; Li, Ping; Liu, Song (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to examine the effect of online verbal aggression on interpersonal trust and the chain-mediating role of core self-evaluation and emotional intelligence among college students.MethodA questionnaire survey was conducted among 869 college students with experiences of online verbal aggression using the Cyber Verbal Bullying Scale, Interpersonal Trust Scale, Core Self-Evaluation Scale, and Emotional Intelligence Scale.Results(1) After controlling other latent variables, it was found that online verbal aggression had a significant direct negative effect on college students’ interpersonal trust. (2) Core self-evaluation and emotional intelligence played significant mediating roles in the relationship between online verbal aggression and interpersonal trust, and their combined chain mediation effect was also statistically significant.ConclusionVictimization by online verbal aggression may lower core self-evaluation in college students, thereby impairing their emotional perception and regulation and ultimately reducing their interpersonal trust. Effective interventions should address self-evaluation, emotional intelligence, and interpersonal trust to mitigate the adverse effects of online verbal aggression on college students.